O processo educativo da costureira industrial: histórias de vida - Bezerra, Germana Maria Fontenelle (1990)
The study analysis the educational process of the textile worker*. This analysis is based upon the concept that education is a way of acquiring knowledge that leads to the subsject's critical conscience as a result of a praxis. Education is considered to be a global process that occurs in different periods of an individual's life involving experiences in formal education, in productive activities as well as in social relations. The study inquires how the worker is able to convert her job as an educational experience that might be used as tool for a transforming action. The study is a qualitative research which utilized a case study in one garment industry in Fortaleza. Reports of participative observations and life reports of three textile workers were used. Life report allowed the researcher tracing the educational process of the textile workers from childhood up to the present time. The study attempted to describe the educational process in a system of capitalistic production not only in the specific training period to perform activities in a fragmented process of garnEnt production. The education of the working class in a system of capitalistic production is only specific qualification for one given operation aiming at productive ability. The focus is on teaching what to do wi thout establishingany relationship between theory and practice. The fragmented knowledgeacquired by the textile worker leads to a fragmented political conscience. This kind of training is reinforced by the dominant ideology whose objective is to reproduce and to *By textile worker is meant a woman who clothing in the Garment industry. makes keep the system. Therefore education in this case is an instrument of capitalistic accumulution which prepares specific hand labor. The education offered, by the owners of theproduction means determines the domineering aspect of the worker class which is taught to perform one single operation in the industry. It is observed, however that the educationalprocess is not completed in the industrial training. Facing a fragmented and alienating professional practice, the worker has possibility to develop critical conscience of ~he productive relations that will lead to the acquisition of a new knowledge which will offer resistance to the system. It my be inferred from the study that in the educational process it is very .important the knowledge articulation in a global way considering specific training and political education. The textile worker's professional formation makes possible the development of resistance to the capitalistic production system in such a way that she acquires both theoretical as well practical knowledge that will lead to a "creative praxis" regarding her job. This fact will give the textileworker condi tions to establish her own business.